2020
DOI: 10.1177/0300060520948754
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of femoral cartilage thickness in healthy adults

Abstract: Objective This study was performed to obtain normative data of the distal femoral cartilage thickness in healthy adults by ultrasound. Methods This cross-sectional study included 72 healthy adults. The demographic characteristics of the participants were recorded, and the thickness of the femoral articular cartilage was measured using a 5- to 18-MHz linear probe. Results Significant statistical difference towards the male side at left medial condyle (P = 0.001) and left lateral condyle (P = 0.009). Weakly posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Te OA group showed a thinner FC in the six measurement locations [10]. When compared to FC thickness among healthy adults, several studies showed thicker mean FC [11,12]. Tese fndings showed a signifcant diference in measurements on the right and left MC sides between the OA and control groups.…”
Section: Resultsmentioning
confidence: 90%
“…Te OA group showed a thinner FC in the six measurement locations [10]. When compared to FC thickness among healthy adults, several studies showed thicker mean FC [11,12]. Tese fndings showed a signifcant diference in measurements on the right and left MC sides between the OA and control groups.…”
Section: Resultsmentioning
confidence: 90%
“…Previous clinical evidence using MRI has revealed sex differences in cartilage at childhood and at early adulthood. [24][25][26][27][28] Moreover, a recent report that analyzed the transcriptome of healthy knee cartilage from men and women revealed 36 sex-specific differential expression genes (DEGs), indicating sex differences at the molecular level. Although the scope of that study was not to compare pre-and postmenopausal age, the donors were young, with an age range of 27 to 57 years for females (n = 5, mean age 42 years), and 18 to 61 years for males (n = 13, mean age 34.5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously investigated the application of 2D US for evaluating femoral condylar cartilage for KOA assessments [ [29] , [30] , [31] , [32] ]. However, quantitative image analysis of non-invasive knee US has only been reported for cartilage thickness measurements but not entire cartilage volumes [ [33] , [34] , [35] ]. Quantitative image analysis may provide more sensitive information regarding early KOA than semi-quantitative grading scales, which are subjective and potentially susceptible to US operator/rater differences.…”
Section: Discussionmentioning
confidence: 99%